A Novel ABCA12 Mutation in Two Families with Congenital Ichthyosis. (31st December 2012) - Walsh, D. M.; Shah, S. H.; Simpson, M. A.; Morgan, N. V.; Khaliq, S.; Trembath, R. C.; Mehdi, S. Q.; Maher, E. R.
Abstract : Autosomal recessive congenital ichthyosis (ARCI) is a rare genetically heterogeneous disorder characterized by hyperkeratosis in addition to dry, scaly skin. There are six genes currently known to be associated with the disease. Exome sequencing data for two affected individuals with ichthyosis from two apparently unrelated consanguineous Pakistani families was analysed. Potential candidate mutations were analysed in additional family members to determine if the putative mutation segregated with disease status. A novel mutation (c.G4676T, p.Gly1559Val) in ABCA12 occurred at a highly conserved residue, segregated with disease status in both families, and was not detected in 143 control chromosomes. Genotyping with microsatellite markers demonstrated a partial common haplotype in the two families, and a common founder mutation could not be excluded. Comparison to previously reported cases was consistent with the hypothesis that severe loss of function ABCA12 mutations are associated with Harlequin Ichthyosis and missense mutations are preferentially associated with milder phenotypes. In addition to identifying a possible founder mutation, this paper illustrates how advances in genome sequencing technologies could be utilised to rapidly elucidate the molecular basis of inherited skin diseases which can be caused by mutations in multiple disease genes.